APPLICATION OF COFFEE PEEL WASTE AS RAW MATERRIAL FOR XYLOOLIGOSACCHARIDE PRODUCTION - Ratnadewi, Anak Agung Istri; Masruroh, Handariatul; ., Suwardiyanto; Santoso, Agung Budi (Coffee Science - ISSN 1984-3909, 2019)
Coffee is the second most common trade commodity in the world after petroleum. The coffee industry generates large amounts of waste in the form of coffee peels. Coffee peel waste consist of lignocellulose containing hemicellulose and other chemical compounds. The objective of this research was to extract xylan, the main component of hemicellulose from coffee waste, and to utilize the xylan in the production of xylooligosaccharide (XOS). Xylan was extracted from coffee waste using NaOH solution and neutralized by HCl 6 M. Afterward, xylan was precipitated using ethanol. Various NaOH concentrations (4, 8, 12 and 16 % w/v) were used to obtain the xylan. NaOH solution with a concentration of 12 % results 43 % extraction of xylan from coffee waste. Xylan obtained from the extraction was hydrolyzed using endo-β-1,4-xylanase from Bacillus sp. to produce XOS. The incubation time of enzyme-substrate was observed at 40 oC, pH 5 and enzyme dose of 23.6 U. Thin layer chromatography results showed that the hydrolyzed products of xylan are XOS with composition xylobiose (X2), xylotriose (X3), xylotetraose (X4) and xylopentaose (X5). LC-MS studies revealed that X2 is the dominant product with the concentration of 6.00 ppm. This research demonstrates the potential to utilizate coffee peel waste as a source of xylan for the production of XOS.